Complete chloroplast genomes from apomictic Taraxacum (Asteraceae): Identity and variation between three microspecies - M Salih, Rubar Hussein; Majeský, Ľuboš; Schwarzacher, Trude; Gornall, Richard; Heslop-Harrison, Pat (PloS one, 2017)
Chloroplast DNA sequences show substantial variation between higher plant species, and less variation within species, so are typically excellent markers to investigate evolutionary, population and genetic relationships and phylogenies. We sequenced the plastomes of Taraxacum obtusifrons Markl. (O978); T. stridulum Trávniček ined. (S3); and T. amplum Markl. (A978), three apomictic triploid (2n = 3x = 24) dandelions from the T. officinale agg. We aimed to characterize the variation in plastomes, define relationships and correlations with the apomictic microspecies status, and refine placement of the microspecies in the evolutionary or phylogenetic context of the Asteraceae. The chloroplast genomes of accessions O978 and S3 were identical and 151,322 bp long (where the nuclear genes are known to show variation), while A978 was 151,349 bp long. All three genomes contained 135 unique genes, with an additional copy of the trnF-GGA gene in the LSC region and 20 duplicated genes in the IR region, along with short repeats, the typical major Inverted Repeats (IR1 and IR2, 24,431bp long), and Large and Small Single Copy regions (LSC 83,889bp and SSC 18,571bp in O978). Between the two Taraxacum plastomes types, we identified 28 SNPs. The distribution of polymorphisms suggests some parts of the Taraxacum plastome are evolving at a slower rate. There was a hemi-nested inversion in the LSC region that is common to Asteraceae, and an SSC inversion from ndhF to rps15 found only in some Asteraceae lineages. A comparative repeat analysis showed variation between Taraxacum and the phylogenetically close genus Lactuca, with many more direct repeats of 40bp or more in Lactuca (1% larger plastome than Taraxacum). When individual genes and non-coding regions were for Asteraceae phylogeny reconstruction, not all showed the same evolutionary scenario suggesting care is needed for interpretation of relationships if a limited number of markers are used. Studying genotypic diversity in plastomes is important to characterize the nature of evolutionary processes in nuclear and cytoplasmic genomes with the different selection pressures, population structures and breeding systems.
Keywords: Taraxacum; Phylogeny; druhová specificita; Genes, Plant; rostlinné geny; molekulární evoluce; genom chloroplastový; Evolution, Molecular; Genome, Chloroplast; jednonukleotidový polymorfismus; Polymorphism, Single Nucleotide; fylogeneze; Species Specificity